Pendampingan Mendongeng dalam Rangka FLS3N Tingkat Nasional SMP Negeri 3 Tugu Trenggalek Tahun 2025 - Fahrudin Fahrudin; Agus Hariadi; Suprapti Suprapti; Putri Iriani Anjakusuma (Masyarakat Mandiri : Jurnal Pengabdian dan Pembangunan Lokal, 2026)
The Community Service Program (PkM) focused on mentoring storytelling competitions was implemented as an effort to improve students' competence in the art of storytelling, while also supporting their preparation for the FLS3N event. The activity was designed through a series of training sessions that included understanding the concept of storytelling, examples of storytelling practices, hands-on practice, and periodic evaluations. During the mentoring process, students showed progress in terms of story mastery, intonation, expression, and confidence. The approach used encouraged active participation so that participants were able to improve their storytelling techniques based on the feedback provided. The results of this activity show that structured and continuous training can improve students' readiness to present stories in a more communicative and interesting manner in upcoming competitions.